POSTGRADUATE PROGRAMS AND DOCTORAL STUDIES IN MODERN CONDITIONS AND A DESTINY OF SKILLS RAISING SYSTEM: ROUND TABLE DISCUSSION - Editorial Article (Moscow Polytechnic University, 2016)
Round table discussion of the journal "Vysshee obrazovanie v Rossii" was heldon March 14 2014 within the framework of the Fourth International regional IGIP conferenceand a methodological seminar of the State Technical University - MADI. The participants were the members of the Editorial Board and the experts in teaching personnel training.Participants: Prikhodko V.M. (Prof., Rector, Moscow Automobile and Road Construction Institute), Zhurakovsky V.M. (Prof., NTF - National Training Foundation), Verbitskiy A.A. (Prof., Sholokhov Moscow State University for the Humanities), Kondrat'ev V.V. (Prof.,Kazan National Research Technological University), Senashenko V.S. (Prof., Peoples FriendshipUniversity of Russia), Bednyi B.I. (Prof., Lobachevsky State University of Nizhni Novgorod), Shestak V.P. (Prof., Financial University under the Government of the RF), Minin M.G. (Prof., National Research Tomsk Polytechnic University), Sazonov B.A. (Prof., The Federal Institute of Development of Education), Medvedev V.E. (Prof., Bauman Moscow State Technical University), Muratova E.I. (Prof., Tambov State Technical University), Krasinskaya L.F. (Prof.,Siberian Transport University), Robotova A.S. (Prof., Herzen State Pedagogical University),Sazonova Z.S. (Prof., Moscow Automobile and Road Construction Institute), Sapunov M.B. (Editor-in-Chief of the journal "Vysshee obrazovanie v Rossii"). The reports of the participants and the discussion between them is presented.